Monitoring and evaluating transition and sustainability of donor-funded programs: Reflections on the Avahan experience. (October 2015) - Bennett, Sara; Ozawa, Sachiko; Rodriguez, Daniela; Paul, Amy; Singh, Kriti; Singh, Suneeta
Highlights: More evaluations of donor transitions are needed to promote understanding of good transition practice; Transition evaluations should document changes that emerge over time in the transition strategy; Our measure of transition readiness was robust and captures key dimensions of transition; More work is required to develop robust measures of institutionalization; Phased transitions allow time for learning and feedback between transition rounds. Transitions involve multiple partners, each are key stakeholders in the evaluation. Abstract: Purpose: In low and middle-income countries, programs funded and implemented by international donors frequently transition to local funding and management, yet such processes are rarely evaluated. We reflect upon experience evaluating the transition of a large scale HIV/AIDS prevention program in India, known as Avahan, in order to draw lessons about transition evaluation approaches and implementation challenges. Results: In terms of conceptualizing the transition theory, the evaluation team identified tensions between the idea of institutionalizing key features of the Avahan program, and ensuring program flexibility to promote sustainability. The transition was planned in three rounds allowing for adaptations to transition intervention and program design during the transition period. The assessment team found it important to track these changes in order to understand which strategies and contextual features supported transition. A mixed methods evaluation was employed, combining semi-structured surveys of transitioning entities (conducted pre and post transition), with longitudinal case studies. Qualitative data helped explain quantitative findings. Measures of transition readiness appeared robust, but we were uncertain of the robustness of institutionalization measures. Finally, challenges to the implementation of such an evaluation are discussed. Conclusions: Given the scarceness of transition evaluations, the lessons from this evaluation may have widespread relevance.